Cyclodextrin-erythromycin complexes as a drug delivery device for orthopedic application - Song W (Dove Medical Press, 2011)
Wei Song1, Xiaowei Yu2, Sunxi Wang5, Ralph Blasier4, David C Markel3, Guangzhao Mao5, Tong Shi1, Weiping Ren1,31Department of Biomedical Engineering, Wayne State University, Detroit, MI, USA; 2Department of Orthopedic Surgery, Second Affiliated Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 3Detroit Medical Center and Providence Hospital Orthopedic Residency, Detroit, 4Orthopedic Section, St Francis Hospital, Escanaba, 5Department of Chemical Engineering, Wayne State University, Detroit, MI, USABackground: Erythromycin, a hydrophobic antibiotic used to treat infectious diseases, is now gaining attention because of its anti-inflammatory effects and ability to inhibit osteoclasts formation. The aim of this study was to explore a cyclodextrin-erythromycin (CD-EM) complex for sustained treatment of orthopedic inflammation.Methods and results: Erythromycin was reacted with ß-cyclodextrin to form a nonhost-guest CD-EM complex using both kneading and stirring approaches. Physiochemical measurement data indicated that erythromycin and cyclodextrin formed a packing complex driven by intermolecular forces instead of a host-guest structure due to the limited space in the inner cavity of ß-cyclodextrin. The CD-EM complex improved the stability of erythromycin in aqueous solution and had a longer duration of bactericidal activity than free erythromycin. Cytotoxicity and cell differentiation were evaluated in both murine MC3T3 preosteoblast cells and RAW 264.7 murine macrophage cells. The CD-EM complex was noncytotoxic and showed significant inhibition of osteoclast formation but had little effect on osteoblast viability and differentiation.Conclusion: These attributes are especially important for the delivery of an adequate amount of erythromycin to the site of periprosthetic inflammation and reducing local inflammation in a sustained manner.Keywords: erythromycin, cyclodextrin, drug stability, bactericidal activity, osteoclastogenesis